Minimum wages and the rise in solo self-employment - Angelika Ganserer; Terry Gregory; Ulrich Zierahn (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Solo self-employment is on the rise despite less favorable working conditions compared to traditional jobs. We show that the introduction of minimum wages in German industries led to an increase in the share of solo self-employment by up to 8.5 percentage points. We explain our findings within a substitution-scale model that predicts a decline in demand and earnings perspectives for high-skilled dependent workers, whenever the negative scale effect (overall decline in industry employment) dominates the positive substitution effect (shift towards high-skilled workers). Such situations can occur during an economic downturn in combination with a strong and rising minimum wage bite.
Keywords: J21; J31; J38; J08; 330; minimum wages; solo self-employment; synthetic control method